Martensitic Stainless Steel JFE410DB-ER with Excellent Heat Resistance for Motorcycle Brake Disks - Yamauchi, Katsuhisa; Ozaki, Yoshihiro; Ujiro, Takumi (Journal of Financial Economics, 2008)
Low carbon martensitic stainless steel JFE410DB-ER with higher heat resistance and corrosion resistance than conventional steels for motorcycle brake disks has been developed. Effects of Nb and N on the heat resistant properties in 12%Cr-1.5%Mn steel were investigated for the purpose of enhancing heat resistance. Addition of Nb introduced fine Nb(C, N), and thereby prevented temper softening. Addition of N decreased the amount of coarse M 23 C 6 and increased the amounts of solute (C + N) and fine Cr 2 (C, N), and thereby prevented temper softening. Additions of Nb and N maintained proper hardness for rotor materials even after tempering at 550°C. Based on these findings, 12%Cr-1.5%Mn-0.13%Nb-0.05%C-0.04%N steel has been developed. The developed steel has excellent durability against temper softening at temperatures exceeding 500°C compared with conventional steels.